Nasi lemak : for the V.I.P. - Alatas, Syed Hussein, Datuk, 1928-2007 (Kuala Lumpur : JB News Media Network, 2004)
Political issues in Malaysia.
In Malay.
Keywords: Politicians -- Malaysia; Malaysia -- Politics and government -- 21st century